KUALITAS AIR BENDUNGAN SUNGAI BADUNG DAN KOLAM PANCING “X” - Dewa Ayu Wahyunia Ratna Dewi; Deny Suhernawan Yusup; Ngurah Intan Wiratmini (SIMBIOSIS, 2025)
The water quality in the northern coastal area of ​​Serangan Island, Denpasar, which receives flow from many large (Tukad) and small (loloan) rivers is indicated to have experienced organic and inorganic pollution including heavy metals. The Badung River Dam and fishing pond "X" located around the northern coastal area of ​​Serangan Island are widely used by the community for fishing activities, so it is necessary to know the quality of the water. The purpose of this study was to determine the water quality of the Badung River dam and the fishing pond "X". The water quality of the Badung River dam has exceeded the threshold of the National Class II water quality standard, DO (1.51 mg/L), pH (5.79), BOD (110.88 mg/L), lead (Pb: 0.24 mg/L) and copper (Cu: 0.29 mg/L) and cadmium (Cd: 0.05 mg/)L. except for water temperature (28oC). Several water quality parameters of the fishing pond “X” have also exceeded the threshold, namely BOD (25.20 mg/L), lead (Pb: 0.05 mg/L), copper (Cu: 0.07 mg/L) and cadmium (Cd: 0.20 mg/L), while the DO parameters (4.33 mg/L), pH (6.26) and water temperature (28.1oC) are still within the threshold range of water quality standards. In general, the water quality of the fishing pond “X” is better than that of the Badung River dam, but monitoring of the heavy metal content (Cd, Pb and Cd) in both waters is needed, which has exceeded the water quality standard class II. Keywords: Ponds, Water quality, Dam Resevoir, Heavy metals, Pollution